1997
DOI: 10.1074/jbc.272.41.25537
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of the Epithelial Sodium Channel Is Regulated by Clathrin-mediated Endocytosis

Abstract: Activity of the epithelial sodium channel (ENaC) is a key determinant of sodium homeostasis and blood pressure. Liddle's syndrome, an inherited form of hypertension, is caused by mutations that delete or alter PY domains in the carboxyl termini of ␤ or ␥ ENaC subunits, leading to increased channel activity. In this study we investigated the mechanism of this effect by analysis of wild-type and mutant ENaC activity in Xenopus oocytes. By inhibiting insertion of new channels into the plasma membrane with brefeld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
221
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(245 citation statements)
references
References 24 publications
21
221
2
1
Order By: Relevance
“…The enhanced rate of decrease of amiloride-sensitive currents in oocytes treated with BFA and ETYA, compared with oocytes treated with BFA alone, provided additional evidence that ETYA reduced functional expression of ENaC by increasing rates of channel endocytosis. Furthermore, a PY motif mutation (␤Y618A) blocked ETYA-mediated inhibition of ENaC expression and is consistent with previous studies that reported that channels with mutations in the PY motif exhibited increased cell surface expression in association with a reduction in the rate of channel endocytosis (21,28,31). Although our results suggest that arachidonic acid inhibits ENaC by reducing surface expression of channels, we cannot discard the possibility that arachidonic acid also reduced channel P o .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The enhanced rate of decrease of amiloride-sensitive currents in oocytes treated with BFA and ETYA, compared with oocytes treated with BFA alone, provided additional evidence that ETYA reduced functional expression of ENaC by increasing rates of channel endocytosis. Furthermore, a PY motif mutation (␤Y618A) blocked ETYA-mediated inhibition of ENaC expression and is consistent with previous studies that reported that channels with mutations in the PY motif exhibited increased cell surface expression in association with a reduction in the rate of channel endocytosis (21,28,31). Although our results suggest that arachidonic acid inhibits ENaC by reducing surface expression of channels, we cannot discard the possibility that arachidonic acid also reduced channel P o .…”
Section: Discussionsupporting
confidence: 78%
“…Stimulation of ENaC endocytosis by arachidonic acid or ETYA appears to be dependent on previously characterized internalization motifs within the C termini of ENaC subunits (21), as substitution of wild type ENaC with the PY mutant ␤Y618A blocks ETYA effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). The ensuing constant inappropriate Na + reabsorption causes volume expansion, even under conditions of high salt intake, and ultimately hypertension (Synder et al 1995;Shimkets et al 1997). A considerable genetic heterogeneity between different mutations and pedigrees has been observed.…”
Section: Liddle's Syndromementioning
confidence: 99%
“…In general, N-glycans on proteins prior to their delivery to the medial Golgi complex are substrates for Endo H, and N-glycans on proteins after passing this point are not substrates. However, not all N-glycans are modified during transit through the Golgi complex, and these N-glycans remain sensitive to treatment with Endo H. ENaC is apparently delivered to the cell surface via the Golgi complex because surface delivery is blocked by treatment of cells with the fungal metabolite brefeldin A that disrupts cytosolic coat assembly needed for vesicle budding throughout the Golgi complex (9,17,18). However, direct evidence for processing of N-glycans on ENaC to complex type is limited.…”
mentioning
confidence: 99%